Structural studies and selected physical investigations of LiCoO2 obtained by combustion synthesis - Michalska, Monika; Ławniczak, Paweł; Strachowski, Tomasz; Ostrowski, Adam; Bednarski, Waldemar (Beilstein Journal of Nanotechnology, 2022)
Nanocrystalline powders of LiCoO2 were synthesized using a modified solution combustion method, and the effects of the annealing temperature (450–900 °C) on structure and composition were investigated using various methods, including XRD, SEM, EPR, and electrical studies. It was found that, as the process temperature increases, the value of the specific surface area decreases, and, hence, the size of the crystallites increases. XRD analysis showed that phase-pure LiCoO2 material was maintained without additional phases. EPR studies revealed the presence of two Ni3+ complexes resulting from Ni impurities. The electrical properties of the studied LiCoO2 samples were investigated by using impedance spectroscopy. Comparison of the effect of annealing temperature on electrical conductivity shows a very interesting behavior. As the annealing temperature increases, the DC conductivity value increases, reaching a maximum at a temperature of 500 °C. However, further increase in the annealing temperature causes a steady decrease in the DC conductivity.
Keywords: lithium cobalt oxide; lithium-ion battery; nanocrystalline powder; solution combustion synthesis

(untitled) - Mizushima, K.; Jones, P. C.; Wiseman, P. J.; Goodenough, J. B. (Mater. Res. Bull., 1980)

(untitled) - Yoshino, A. (Angew. Chem., Int. Ed., 2012)

Progress in Batteries and Solar Cells - Nagaura, T.; Tozawa, K. (Lithium ion rechargeable battery, 1990)
https://jglobal.jst.go.jp/en/detail?JGLOBAL_ID=200902083334341504&rel=1#%7B

(untitled) - Ozawa, K. (Solid State Ionics, 1994)

(untitled) - Shukla, A. K.; Kumar, T. P. (Curr. Sci., 2008)

(untitled) - Nitta, N.; Wu, F.; Lee, J. T.; Yushin, G. (Mater. Today, 2015)

(untitled) - Xu, X.; Lee, S.; Jeong, S.; Kim, Y.; Cho, J. (Mater. Today, 2013)

Lithium Batteries Science and technology - Nazri, G.-A.; Pistoia, G. (Springer, 2003)

(untitled) - Fergus, J. W. (J. Power Sources, 2010)

(untitled) - Zou, M.; Yoshio, M.; Gopukumar, S.; Yamaki, J.-i. (Chem. Mater., 2003)

(untitled) - Zou, M.; Yoshio, M.; Gopukumar, S.; Yamaki, J.-i. (Mater. Res. Bull., 2005)

(untitled) - Zou, M.; Yoshio, M.; Gopukumar, S.; Yamaki, J.-i. (Chem. Mater., 2005)

(untitled) - Sun, Y.-K.; Chen, Z.; Noh, H.-J.; Lee, D.-J.; Jung, H.-G.; Ren, Y.; Wang, S.; Yoon, C. S.; Myung, S.-T.; Amine, K. (Nat. Mater., 2012)

(untitled) - Jyoti, J.; Singh, B. P.; Tripathi, S. K. (J. Energy Storage, 2021)

(untitled) - Mauger, A.; Julien, C. (Ionics, 2014)

(untitled) - Fu, L. J.; Liu, H.; Li, C.; Wu, Y. P.; Rahm, E.; Holze, R.; Wu, H. Q. (Solid State Sci., 2006)

(untitled) - Ohzuku, T.; Makimura, Y. (Chem. Lett., 2001)

(untitled) - Jo, M.; Jeong, S.; Cho, J. (Electrochem. Commun., 2010)

(untitled) - Li, Z.; Ban, C.; Chernova, N. A.; Wu, Z.; Upreti, S.; Dillon, A.; Whittingham, M. S. (J. Power Sources, 2014)

(untitled) - Needham, S. A.; Wang, G. X.; Liu, H. K.; Drozd, V. A.; Liu, R. S. (J. Power Sources, 2007)

(untitled) - Adipranoto, D. S.; Ishigaki, T.; Hoshikawa, A.; Iwase, K.; Yonemura, M.; Mori, K.; Kamiyama, T.; Morii, Y.; Hayashi, M. (Solid State Ionics, 2014)

(untitled) - Caballero, A.; Hernán, L.; Morales, J.; Castellón, E. R.; Santos, J. (J. Power Sources, 2004)

(untitled) - Jiang, C.; Hosono, E.; Zhou, H. (Nano Today, 2006)

(untitled) - Lee, K. T.; Cho, J. (Nano Today, 2011)

(untitled) - Wang, Y.; Li, H.; He, P.; Hosono, E.; Zhou, H. (Nanoscale, 2010)

(untitled) - Michalska, M.; Lipińska, L.; Sikora, A.; Ziółkowska, D.; Korona, K. P.; Andrzejczuk, M. (J. Alloys Compd., 2015)

(untitled) - Michalska, M.; Hamankiewicz, B.; Ziółkowska, D.; Krajewski, M.; Lipińska, L.; Andrzejczuk, M.; Czerwiński, A. (Electrochim. Acta, 2014)

(untitled) - Krajewski, M.; Michalska, M.; Hamankiewicz, B.; Ziolkowska, D.; Korona, K. P.; Jasinski, J. B.; Kaminska, M.; Lipinska, L.; Czerwinski, A. (J. Power Sources, 2014)

(untitled) - Hamankiewicz, B.; Michalska, M.; Krajewski, M.; Ziolkowska, D.; Lipińska, L.; Korona, K.; Kaminska, M.; Czerwinski, A. (Solid State Ionics, 2014)

(untitled) - Jasinski, J. B.; Ziolkowska, D.; Michalska, M.; Lipinska, L.; Korona, K. P.; Kamińska, M. (RSC Adv., 2013)

(untitled) - Michalska, M.; Lipińska, L.; Mirkowska, M.; Aksienionek, M.; Diduszko, R.; Wasiucionek, M. (Solid State Ionics, 2011)

(untitled) - Fitriani; Ovik, R.; Long, B. D.; Barma, M. C.; Riaz, M.; Sabri, M. F. M.; Said, S. M.; Saidur, R. (Renewable Sustainable Energy Rev., 2016)

(untitled) - Li, G.; Zhang, J. (Appl. Surf. Sci., 2012)

(untitled) - Zhu, C.; Yang, C.; Yang, W.-D.; Hsieh, C.-Y.; Ysai, H.-M.; Chen, Y.-S. (J. Alloys Compd., 2010)

(untitled) - Gao, S.; Wei, W.; Ma, M.; Qi, J.; Yang, J.; Chu, S.; Zhang, J.; Guo, L. (RSC Adv., 2015)

(untitled) - Larcher, D.; Delobel, B.; Dantras-Laffont, L.; Simon, E.; Blach, J.-F.; Baudrin, E. (Inorg. Chem., 2010)

(untitled) - Shin, Y. H.; Koo, S.-M.; Kim, D. S.; Lee, Y.-H.; Veriansyah, B.; Kim, J.; Lee, Y.-W. (J. Supercrit. Fluids, 2009)

(untitled) - Song, S.-W.; Han, K.-S.; Yoshimura, M. (J. Am. Ceram. Soc., 2000)

(untitled) - Burukhin, A.; Brylev, O.; Hany, P.; Churagulov, B. R. (Solid State Ionics, 2002)

(untitled) - Kim, D. Y.; Ju, S. H.; Kang, Y. C. (Mater. Res. Bull., 2007)

(untitled) - Choi, K. Y.; Kim, K. D.; Yang, J. W. (J. Mater. Process. Technol., 2006)

(untitled) - Kondo, A.; Nakamura, E.; Kozawa, T.; Abe, H.; Naito, M.; Yoshida, J.; Nakanishi, S.; Iba, H. (Adv. Powder Technol., 2014)

(untitled) - Xuanye, Y.; Hongge, Y.; Jihua, C.; Mao, H.; Feng, X.; Zhengfu, Z.; Hongmei, X. (Solid State Ionics, 2016)

(untitled) - Yan, H.; Huang, X.; Lu, Z.; Huang, H.; Xue, R.; Chen, L. (J. Power Sources, 1997)

(untitled) - Yan, H.; Huang, X.; Li, H.; Chen, L. (Solid State Ionics, 1998)

(untitled) - Subramanian, V.; Chen, C. L.; Chou, H. S.; Fey, G. T. K. (J. Mater. Chem., 2001)

(untitled) - Gonzalo, E. C.; Morán, E.; Parada, C.; Ehrenberg, H. (Mater. Chem. Phys., 2010)

(untitled) - Aruna, S. T.; Mukasyan, A. S. (Curr. Opin. Solid State Mater. Sci., 2008)

(untitled) - Julien, C. (Ionics, 2000)

(untitled) - Varma, A.; Mukasyan, A. S.; Rogachev, A. S.; Manukyan, K. V. (Chem. Rev., 2016)

(untitled) - Mukasyan, A. S.; Epstein, P.; Dinka, P. (Proc. Combust. Inst., 2007)

(untitled) - Hwang, C.-C.; Wu, T.-Y.; Wan, J.; Tsai, J.-S. (Mater. Sci. Eng., B, 2004)

(untitled) - Wen, W.; Wu, J.-M. (RSC Adv., 2014)

(untitled) - Li, F.-t.; Ran, J.; Jaroniec, M.; Qiao, S. Z. (Nanoscale, 2015)

(untitled) - Vivekanandhan, S.; Venkateswarlu, M.; Satyanarayana, N. (Mater. Chem. Phys., 2008)

(untitled) - Santiago, E. I.; Andrade, A. V. C.; Paiva-Santos, C. O.; Bulhões, L. O. S. (Solid State Ionics, 2003)

(untitled) - Kalyani, P.; Kalaiselvi, N.; Muniyandi, N. (J. Power Sources, 2002)

(untitled) - Ghosh, P.; Mahanty, S.; Basu, R. N. (Mater. Chem. Phys., 2008)

(untitled) - Rodrigues, S.; Munichandraiah, N.; Shukla, A. K. (J. Power Sources, 2001)

(untitled) - Strachowski, T.; Woluntarski, M.; Djas, M.; Kowiorski, K.; Wiliński, Z.; Baran, M.; Jagiełło, J.; Winkowska, M.; Lipińska, L. (Electron. Mater., 2017)

(untitled) - Stoll, S.; Schweiger, A. (J. Magn. Reson., 2006)

(untitled) - Mai, V. C.; Bednarski, W.; Borowiak-Sobkowiak, B.; Wilkaniec, B.; Samardakiewicz, S.; Morkunas, I. (Phytochemistry, 2013)

(untitled) - Stoyanova, R.; Zhecheva, E.; Alcántara, R.; Lavela, P.; Tirado, J. L. (Solid State Commun., 1997)

(untitled) - Antolini, E. (Solid State Ionics, 2004)

(untitled) - Han, C.-H.; Hong, Y.-S.; Park, C. M.; Kim, K. (J. Power Sources, 2001)

Impedance Spectroscopy Theory, Experiment, and Applications - Barsoukov, E.; Macdonald, J. R. (John Wiley & Sons, 2005)

(untitled) - Ławniczak, P.; Pogorzelec-Glaser, K.; Pietraszko, A.; Hilczer, B. (Acta Crystallogr., Sect. B: Struct. Sci., Cryst. Eng. Mater., 2021)

(untitled) - Levasseur, S.; Ménétrier, M.; Delmas, C. (Chem. Mater., 2002)